Particularidades do processo de evasão: uma amostragem da turma de Letras Alemão de 2017 da UFPA - FERREIRA, Glória Jéssica Carvalho (2024)
This project was elaborated as a way to identify the factors that contribute to dropout, in order to analyze the students' reality, their perceptions and experiences as students of the German Letters Course at UFPA, and to propose viable contours for the problem considering not only the existing limitations, but also the principles and mission of UFPA, thinking about the reduction of evasion in the Course and also in the transformations and demands in the face of globalization and innovations in the current world. For this, a Questionnaire with open questions was elaborated and applied to a pre-defined group through compatibility with previously recommended standards. Their themes revolved around some personal data, their lived experiences, their perceptions about evasion and motivations, and finally their personal suggestions regarding the improvement of our Course. The result of this field analysis was theoretically used to understand the most common reasons that condition students to opt for evasion; evaluation of the feedback received on actions aimed at training future criticalreflective professionals in the area, through the transformations and scientific and technological innovations in which students are inserted; identify alternatives that work around and provide the improvement of the Course seeking prevention, correction and, consequently, reduction of dropout rates. Although this university dropout problem is far from being resolved, seeking updates and modernizing the system to keep up with the demands and innovations of today's world - and of the future - not only guarantees a greater permanence of future students, but also bringing greater visibility to the Course; offers continuing education and work in the field; highlights the value of mastering a Foreign Language (FL) in academia, as well as its relevance as an essential tool nowadays; among other benefits. Finally, as final considerations, we understand that the performance of the FL professional depends significantly on their training, without ceasing to be a continuous and autonomous process.